2018
DOI: 10.1186/s12885-018-4922-4
|View full text |Cite
|
Sign up to set email alerts
|

The oncogene KRAS promotes cancer cell dissemination by stabilizing spheroid formation via the MEK pathway

Abstract: BackgroundPeritoneal dissemination is a critical prognostic factor in ovarian cancer. Although stabilized spheroid formation promotes cancer cell peritoneal dissemination in ovarian cancer, the associated oncogenes are unknown. In this study, we assessed the role of the KRAS oncogene in ovarian cancer cell dissemination, focusing on the stability of cells in spheroid condition, as well as the modulation of intracellular signaling following spheroid transformation.MethodsWe used ID8, a murine ovarian cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…Thus, other factors must explain the stemness attributes in these cells. Other candidates affecting self-renewal include MYC, EGFR, RAS, and EZH2 [ 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, other factors must explain the stemness attributes in these cells. Other candidates affecting self-renewal include MYC, EGFR, RAS, and EZH2 [ 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jones, et al suggested that metastatic type 1 ovarian cancer with KRAS mutation has a poor prognosis (9). A recent study indicated that KRAS promoted ovarian cancer dissemination by stabilizing spheroid formation (10). Through oncomine analysis, the current study results suggested that patients with KRAS mutation status displayed higher expression levels of AURKA, BUB1, BUB1B, CDK1 and CCNA2 than those with KRAS wild type status.…”
Section: Discussionmentioning
confidence: 48%
“…The KRAS gene, a crucial molecule in the major intracellular signaling pathways (such as the EGFR and the mitogen activated protein kinase/ extracellular signal-regulated kinase (MAPK/ERK) signaling pathways), exerts substantial regulatory effects on multiple tumors. For example, its proteins can promote the growth (11) and metastasis (12,13) of most tumors and serve as the evaluation indexes for chemotherapy in pancreatic cancer (14). The KRAS gene has an elevated mutation rate in some tumors, which may regulate important signaling pathways and protein networks (15).…”
Section: Discussionmentioning
confidence: 99%